Măsurile provizorii ordonate de către Curtea Internațională de Justiție în cazurile privind aplicarea forței în dreptul internațional - Roșca, Valentin (Tipografia "Foxtrot",Bălți, 2016)
In case the UN Security Council faces an international dispute, the UN Charter (Article 36) prescribes that the legal disputes must undergo the judicial procedure of the International Court of Justice. By this provision, the UN Charter operates a division of competence between the UN Security Council and the International Court of Justice in the matter of settlement of international disputes. By the start of the examination of a case the International Court of Justice has a possibility of involvement and imposing conditions in an international dispute and, even, to begin a peaceful settlement of an armed conflict, including through the application of interim measures in a particular case.
Keywords: International dispute; judicial procedure; UN Charter; International Court of Justice; UN Security Council; competence; peaceful settlement; armed conflicts; interim measures